2022
DOI: 10.3390/app12020789
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary Sinusitis as a Complication of Zygomatic Implants Placement: A Narrative Review

Abstract: Aims: The aim of this review is to consider maxillary sinusitis as a complication of zygomatic implants placements. Maxillary sinusitis a common complication but in the literature there are no reviews that focus only on this condition and its possible treatment. This review was carried out with to highlight the main findings of the literature on this topic and to improve knowledge in this field. Methods: The search strategy resulted in 155 papers. After selection of the inclusion criteria only 11 papers were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Moreover, in some anatomical situations, the extra-maxillary technique allows maintaining the sinus membrane intact and thus avoids rhinosinusal complications. Finally, a prosthetic-driven implant positioning with an optimized biomechanical design of the prosthesis is expected to reduce prosthetic complications [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in some anatomical situations, the extra-maxillary technique allows maintaining the sinus membrane intact and thus avoids rhinosinusal complications. Finally, a prosthetic-driven implant positioning with an optimized biomechanical design of the prosthesis is expected to reduce prosthetic complications [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nocini systematically reviewed maxillary sinusitis as a complication of zygomatic implant placements in 11 papers, and found that 12.3% patients presented maxillary sinusitis. 9 However, only 4 studies evaluated sinusitis (both clinical and radiological evaluations). The most common treatment was antibiotics alone or combined with FESS.…”
Section: Prevention Of Sinusitis In Zygomatic Implant Surgerymentioning
confidence: 99%
“…Zygomatic implants have demonstrated their effectiveness as a viable solution in addressing the challenges of managing atrophic edentulous maxilla [3][4][5][6] and maxillectomy defects [7]. Brånemark introduced these implants to cater to patients requiring prosthetic rehabilitation due to extensive maxillary defects resulting from tumor resections, trauma, and congenital issues [8].…”
Section: Introductionmentioning
confidence: 99%